PREVALENCE OF MALARIA, THE EFFECT OF PARASITAEMIA ON BLOOD PARAMETERS AND IRON LEVEL OF INFECTED CHILDREN UNDER FIVE YEARS OF AGE IN ITU, SOUTH-SOUTH, NIGERIA - Bassey, Bassey Eyibio; Etefia, Ekaette Victor; Adams , Ekamma Godwin; Akpan, Mfonobong Edo (FUDMA JOURNAL OF SCIENCES, 2024)
Infection due to malaria constitutes a devastating health concern in Itu with varied haematological implications. To determine the status of the infection, the effect of parasites on some haematological parameters, and serum iron level of infected children under 5 in Itu Local Government Area, Nigeria, a cross-sectional study involving 430 children was conducted. Samples were collected from subjects following obtaining consent from caregivers. Malaria prevalence and parasitaemia level was diagnosed microscopically. Haematology auto-analyzer was used to determine haematological parameters. Hitachi 912 analyzer was used to determine serum iron levels from the samples. Malaria prevalence of 41.08% was recorded in the study. The highest prevalence (42.86%) was reported among the female subjects. The mean level of haemoglobin, packed cell volume, red blood cell level, lymphocyte, monocytes, and eosinophil count, decreases significantly (p < 0.05) in infected children and the mean level of neutrophil, as well as white blood cell count, increases compared to the non-infected subjects. A weak correlation between the level of parasite load and Hb (r= 0.108), PCV(r=0.247), and RBC (r= o.074) was also reported. The study recorded a higher mean serum ferritin level (648 ng/ml) compared to non-infected, lower mean serum transferrin (6.41 ng/ml) compared to normal, and mean serum iron (54.40 ng/ml) was higher than normal. Therefore, it is essential to pay keen attention to these blood indices in the management of malaria among under 5 children in the study area